Optimizing carrot extract serum (Daucus carota L.) for anti-aging: efficacy in moisturizing and pore size reduction using Box-Behnken design method - Iskandar, Benni; Antasya, Vaylia; Nasution, Musyirna Rahmah; Frimayanti, Neni; Peng-Wei, Ching; Khairani, Sondang (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Carrot extract (Daucus carota L.) contains various bioactive compounds, including vitamins A, B, and C, alkaloids, flavonoids, tannins, anthraquinones, saponins, diterpenes, steroids, beta-carotene, phenols, terpenoids, and minerals, all of which possess antioxidant properties. These compounds are known to help slow down the aging process. The aim of this study was to determine the optimal concentrations of gelling and alkalizing agents, assess their interactions, and evaluate the anti-aging effects of the most effective serum formulation. The formulation was optimized using the Box–Behnken design with two key factors: Carbopol 940 concentration (0.5–1%) and triethanolamine (0.5–1%). The effects on pH, adhesion, and spreadability were evaluated. The best formulation was achieved with 0.837% Carbopol 940 and 0.855% triethanolamine, showing a pH error of 2.45%, adhesion error of 0.76%, and spreadability error of 1.01%, all within acceptable limits (errors < 10%). After four weeks of stability testing, the formulation remained stable, well-mixed, with a pH of 5.16, an adhesion time of 1.60 seconds, and spreadability of 6.73 cm, with no discomfort. The combination of Carbopol 940 and triethanolamine improved the physical properties, enhancing anti-aging effects compared to the base formula. The optimized serum increased skin moisture by 84.62%, reduced pore size by 64.71%, lightened spots by 62.79%, and reduced wrinkles by 67.50%. This indicates the optimized carrot extract serum is stable, safe, and effective as an anti-aging agent, making it a promising natural skincare product.